IMPLEMENTASI AUDITORY INTELLECTUALLY REPETITION (AIR) BERBANTUAN VIDEO INTERAKTIF VIINCAH TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Mukharomagh Firoh, Neli; Roestika Rini, Zulmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills are one of the essential competencies that elementary school students need to develop in mathematics learning. However, students' critical thinking skills remain relatively low due to the limited use of innovative learning models and interactive learning media. This study aimed to determine the differences and the effect of the Auditory Intellectually Repetition (AIR) learning model assisted by Video Interaktif Bilangan Cacah (VIINCAH) on the critical thinking skills of fifth-grade elementary school students. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The study was conducted at SD Negeri Klepu 03 as the experimental class and SD Negeri Klepu 01 as the control class. Data were collected through tests, observations, questionnaires, interviews, and documentation. The data were analyzed using normality and homogeneity tests, Independent Sample t-test, and simple linear regression. The results showed a significant difference in students' critical thinking skills between the experimental and control classes, as indicated by the Independent Sample t-test with a significance value of 0.000 (<0.05). The experimental class achieved a higher posttest mean score (79.50) than the control class (61.69). Furthermore, the regression analysis showed a significance value of 0.000 with an R Square value of 0.588, indicating that the AIR learning model assisted by VIINCAH contributed 58.8% to students' critical thinking skills. Therefore, the AIR learning model assisted by VIINCAH is effective in improving elementary school students' mathematical critical thinking skills